High energy redshifted and enhanced spectral broadening by molecular alignment - Fan, G.; Safaei, R.; Kwon, Ojoon; Schuster,; Legare, Katherine; Lassonde, P.; Ehteshami, A.; Arias, Loic; Laramee, A.; Beaudoin-Bertrand, J.; Limpert, Jens; Tao, Zhensheng; et al. (Optics Letters, 2020)
We demonstrate an efficient approach for enhancing the spectral broadening of long laser pulses and for efficient frequency redshifting by exploiting the intrinsic temporal properties of molecular alignment inside a gas-filled hollow-core fiber (HCF). We find that laser-induced alignment with durations comparable to the characteristic rotational time scale TRotAlign enhances the efficiency of redshifted spectral broadening compared to noble gases. The applicability of this approach to Yb lasers with (few hundred femtoseconds) long pulse duration is illustrated, for which efficient broadening based on conventional Kerr nonlinearity is challenging to achieve. Furthermore, this approach proposes a practical solution for high energy broadband long-wavelength light sources, and it is attractive for many strong field applications.
CRIS-Team Scopus Importer:2023-04-20